PENGELOLAAN BUMDES BABUSSALAM SEJAHTERA DIDESA BABUSSALAM KECAMATAN RAMBAH KABUPATEN ROKAN HULU TAHUN 2021-2022 - Ridho Agusta; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This thesis discusses the management of BUMDES Babussalam Sejahtera which has three business units, namely organic fertilizer, brick and date agrotourism waterpark. The problem in this research is how the BUMDes Babussalam is managed, but it is not directly proportional to business units that are no longer actively running and are starting to not be managed well. This research aims to analyze the Management of BUMDes Babussalam Sejahtera in Babussalam Village, Rambah District, Rokan Hulu Regency in 2021-2022. This research approach is qualitative with descriptive research type. The research location is in Rokan Hulu Regency. Data collection using interview and documentation techniques. Data analysis techniques using qualitative analysis techniques. Researchers use George R. Terry's (2006) theory regarding the 4 management functions known as POAC, namely Planning, Organizing, Actuating, Controlling. The results of this research are that the management of the BUMDes Babussalam Sejahtera business unit has gone through the planning stage well by looking at several aspects, but the organizing stage has not gone well because several responsibilities have not been carried out well. stages of directing on the road well so that all forms of management can run well and the goals that have been set run as expected. and the supervision stages are carried out well so that all problems in the management of the business unit can be minimized. The conclusion of this research is that BUMDes Babussalam Sejahtera uses 4 stages of management functions in managing 3 business units, namely organic fertilizer, Batako, and Date Palm Agrotourism Waterpark, but the three business units are not running well and the Batako program is no longer operational. Keywords: Management, Planning, Organizing, Directing, Supervising